A Rapid Self-Assembly Peptide Hydrogel for Recruitment and Activation of Immune Cells - Ruyue Luo; Yuan Wan; Xinyi Luo; Guicen Liu; Zhaoxu Li; Jialei Chen; Di Su; Na Lu; Zhongli Luo (Molecules, 2022)
Self-assembly peptide nanotechnology has attracted much attention due to its regular and orderly structure and diverse functions. Most of the existing self-assembly peptides can form aggregates with specific structures only under specific conditions and their assembly time is relatively long. They have good biocompatibility but no immunogenicity. To optimize it, a self-assembly peptide named DRF3 was designed. It contains a hydrophilic and hydrophobic surface, using two N-terminal arginines, leucine, and two c-terminal aspartate and glutamic acid. Meanwhile, the c-terminal of the peptide was amidated, so that peptide segments were interconnected to increase diversity. Its characterization, biocompatibility, controlled release effect on antigen, immune cell recruitment ability, and antitumor properties were examined here. Congo red/aniline blue staining revealed that peptide hydrogel DRF3 could be immediately gelled in PBS. The stable β-sheet secondary structure of DRF3 was confirmed by circular dichroism spectrum and IR spectra. The observation results of cryo-scanning electron microscopy, transmission electron microscopy, and atomic force microscopy demonstrated that DRF3 formed nanotubule-like and vesicular structures in PBS, and these structures interlaced with each other to form ordered three-dimensional nanofiber structures. Meanwhile, DRF3 showed excellent biocompatibility, could sustainably and slowly release antigens, recruit dendritic cells and promote the maturation of dendritic cells (DCs) in vitro. In addition, DRF3 has a strong inhibitory effect on clear renal cell carcinoma (786-0). These results provide a reliable basis for the application of peptide hydrogels in biomedical and preclinical trials.